The case of EFL: does technology lead to learning? - Vieira, Gicele Vergine; Finardi, Kyria Rebeca (Raído, 2018)
This paper reviewed a series of studies which investigated the validity of educational soft ware as tools to promote EFL learning. A metasummary approach was used to appraise and synthesize the main fi ndings of four studies. The results are presented in a comparative form, providing information extracted from each report in the following domains: objectives of the studies, instruments of data collection, sample composition, theoretical background, major fi ndings and conclusions and implications of the studies. It is concluded that the four studies reviewed do believe in the contribution of technology to EFL teaching and learning but express a concern about the integration of human-computer interaction and pedagogic features of educational soft ware for EFL learning.